An Increased Rate for Major Birth Anomalies was not Found Following Dental Treatment Requiring Local Anesthesia During Pregnancy - Moore, Paul A. (The journal of evidence-based dental practice, 2016)
Pregnancy outcome after in utero exposure to local anesthetics as part of dental treatment: a prospective comparative cohort study. Hagai A, Diav-Citrin O, Shechtman S, Ornoy A. J Am Dent Assoc 2015;146(8):572-80. Not reported Comparative cohort study